Effect of Dried Distillers Grains With Solubles and Red Osier Dogwood Extract on Fermentation Pattern and Microbial Profiles of a High-Grain Diet in an Artificial Rumen System - Gomaa, Walaa Mohamed Sayed; Saleem, Atef Mohamed; Ran, Tao; Jin, Long; Samir, Mohamed; McGeough, Emma J.; Ominski, Kim; Chen, Lingyun; Yang, Wenzhu (Frontiers in Veterinary Science, 2021)
The objective of this study was to evaluate the effect of dried distillers grain with solubles (DDGS) and red osier dogwood (ROD) extract on in vitro fermentation characteristics, nutrient disappearance and microbial profiles using the rumen simulated technique. The experiment was a completely randomized design with a 2 × 2 factorial arrangement of treatments and 4 replicates per treatment. A basal diet (10% barley silage, 87% dry-rolled barley grain and 3% vitamin and mineral supplement, dry matter [DM] basis) and a DDGS diet (as per basal with 25% wheat DDGS replacing an equal portion of barley grain) were supplemented with ROD extract at 0 and 1% (DM basis). The experimental period consisted of 10 d of adaptation and 7 d of data and sample collection. The substitution of wheat DDGS for barley grain did not affect gas production, disappearances of DM, organic matter and crude protein, total volatile fatty acid (VFA) production, and microbial protein production. However, replacing barley grain with wheat DDGS increased (P = 0.01) fermenter pH and molar proportion of branched-chain VFA, and tended (P = 0.06) to switch the fermentation pattern to more acetate production due to increased (P = 0.01) NDF disappearance, and tended (P = 0.08) to decrease CH4 production. In the basal barley diet, ROD extract tended to increase A:P ratio (P = 0.08) and to decrease starch disappearance (P = 0.06) with no effect on other variables. No effects of ROD in the DDGS diet were observed. Numbers of OTUs and Shannon diversity index of the microbial community did not differ among treatments. Taxonomic analysis revealed no effect of adding ROD extract on the relative abundance of bacteria at the phylum level with either the basal or DDGS diets, while at the genus level, microbial community was affected by both DDGS and ROD extract addition. These results indicated that the substitution of wheat DDGS for barley grain may mitigate CH4 emissions. The trend of reduced starch fermentability and increased NDF disappearance with ROD extract, suggest a reduced risk of rumen acidosis and to improve fiber utilization for cattle fed high grain diet.